2013
DOI: 10.1002/jts.21814
|View full text |Cite
|
Sign up to set email alerts
|

The Co‐Occurrence of Major Depressive Disorder Among Individuals With Posttraumatic Stress Disorder: A Meta‐Analysis

Abstract: Although co-occurring posttraumatic stress disorder (PTSD) and major depressive disorder (MDD) is associated with greater distress, impairment, and health care utilization than PTSD alone, the magnitude of this problem is uncertain. This meta-analysis aimed to estimate the mean prevalence of current MDD co-occurrence among individuals with PTSD and examine potential moderating variables (U.S. nationality, gender, trauma type, military service, referral type) that may influence the rate of PTSD and MDD co-occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

37
310
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 523 publications
(370 citation statements)
references
References 116 publications
37
310
2
5
Order By: Relevance
“…Although most individuals experience psychological distress subsequent to trauma, only a substantial minority go on to develop PTSD, with the cross-national lifetime prevalence being 3.9% in the total sample and 5.6% among the trauma-exposed (Koenen et al, 2017). PTSD and MDD are highly comorbid, as shown by a recent meta-analysis that 52% of individuals with current PTSD had co-occurring MDD (Rytwinski, Scur, Feeny, & Youngstrom, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Although most individuals experience psychological distress subsequent to trauma, only a substantial minority go on to develop PTSD, with the cross-national lifetime prevalence being 3.9% in the total sample and 5.6% among the trauma-exposed (Koenen et al, 2017). PTSD and MDD are highly comorbid, as shown by a recent meta-analysis that 52% of individuals with current PTSD had co-occurring MDD (Rytwinski, Scur, Feeny, & Youngstrom, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…A recent large meta-analysis composed of 57 studies, across both military and civilian samples, reported a comorbidity rate of 52 percent [2]. The underlying reason for this high degree of comorbidity is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The same authors 67,68 found that gender was not significantly connected to the co-occurrence of depression and PTSD. This may also have clinical significance because it is known that irritability and hostility are frequent depressive symptoms, particularly in men, constituting a clinical picture that could be confused with PTSD, 69 thus making it harder to arrive at a valid diagnosis of depression.…”
Section: Depression and Ptsdmentioning
confidence: 95%
“…65,66 A meta-analysis conducted by Rytwinski et al 67 found that the average co-occurrence of depression in people with PTSD was 52%, and that depression is 4 times more frequent in individuals already diagnosed with PTSD, regardless of place of residence. In the Medellin analyses, major depression was the only variable that showed a significant predictive relationship to PTSD.…”
Section: Depression and Ptsdmentioning
confidence: 99%
See 1 more Smart Citation